Bacterial contamination of ram semen used for artificial insemination in indigenous ewes (Bangladesh Veterinarian, 2018)
Ram semen was assessed for quality and presence of bacteria. Four ejaculates were collected from each of four rams twice a week using artificial vagina. The volume varied from 0.4 - 1.3 mL, colour from 2 - 4 (creamy to creamy-grey), mass activity from 3 - 5, sperm motility from 75 - 85%, viability from 80 - 95%, and concentration from, 2500 - 5000 × 106/mL. The mass activity of ram R6 was significantly (P